Estudios sobre la Universidad de Tarragona (1572-1717) - Ramis-Barceló, Rafael (Historia de las Universidades, 2022)
This book collects various studies on diferent periods in the history of the University of Tarragona (1572-1717), especially its founding and initial stage, which provides innovative documentation on professors, degrees and about university finances. It is a small contribution, which complements some previous works, and it provides certain new materials that help to know the evolution of this University.